Hematological and Renal Function Evaluation in Dogs with IMHA - Moraes, Livia Fagundes [UNESP]; Takahira, Regina Kiomi [UNESP]; Golim, Marjorie de Assis [UNESP] (Univ Fed Rio Grande Do Sul, 2017)
Background: The IMHA is a common cause of anemia in dogs and characterized by direct destruction or phagocytosis of erythrocytes opsonized by IgG, IgM and/or complement. The diagnosis is based on the identification of erythrocytes destruction in the presence of anti-erythrocyte antibodies, producing spherocytes, auto-agglutination, Coomb's test or flow cytometry test positive, in addition to anemia and clinical signs of hemolysis. The renal biochemical profile and urinalysis may reveal important changes due to the severity of the kidney demage. The aim of this study were to evaluate the incidence of hematological and renal abnormalities, and the prevalence of immunoglobulin's classes involved in IMHA. Materials, Methods & Results: In a total of 87 anemic dogs were selected and tested by Coomb's test, flow cytometry (FC), and auto-agglutination, along with CBC, reticulocyte count, renal profile (ureia and creatinine), hemoparasite search in peripheral blood smears, and Ehrlichia sp. and leptospirosis tests. The results were analyzed by t test or Mann-Whitney with 5% of significance. Therefore, 61 dogs (70.11%) were positive for IMHA by FC, 31 (35.63%) by Coomb's test, and 24 (27.58%) by auto-agglutination. There was not a predominance of IgG or IgM involvement. The hematological and clinical changes in dogs with IMHA included macrocytic, hypochromic regenerative anemia, and reticulocytosis, as well as icterus, fever, auto-agglutination, hyperglobulinemia and bilirrubinuria. Spherocytosis was found in 9.8% of dogs with IMHA, and 29.5% of dogs had leukocytosis, 39.6% neutrophilia, and 72.1% thrombocytopenia. Mostly of cases of IHMA (74.6%) were attributed to infectious diseases and associated with Ehrlichia sp. (secondary IMHA), 21.4% of dogs with IMHA had azotemia, and 51.8% had increased urine protein creatinine ratio. Discussion: The FC was confirmed as a more sensitive technique for the diagnosis of IMHA compared to auto-agglutination and Coomb's tests. The auto-agglutination test was more specific than the Coomb's test, however the last one was more sensitive. The similar prevalence of IgG and IgM in IMHA did not indicate which class of immunoglobulin would be a better choice for diagnosis by the FC technique. Antibodies are produced against normal red cells (primary or idiopathic IMHA) or to red cells that are antigenical changed by the action of drugs, neoplasia or infectious diseases (leptospirosis, babesiosis, canine ehrlichiosis), known as secondary IMHA. This study alerts for the high prevalence of IMHA in dogs, in most cases characterized by a regenerative anemia associated with intense thrombocytopenia and secondary to Ehrlichia sp. in areas endemic to this infectious disease. In Brazil, the presence of endemic areas for various infectious diseases may contribute to the high prevalence of secondary IMHA. Kidney damage may occurs because tissue hypoxia increases the risk of progressive injury, due to acute hematocrit decrease (below 22%), leading to renal tubular necrosis, whereas the deposition of immune complexes, mainly in the renal parenchyma, may aggravate the renal injury, further complicating the clinical state of the animal. Direct renal injury caused by crystallization of free hemoglobin in the renal tubules may result in renal azotemia. Hypoxia and nephrotoxicity caused by hemoglobinemia reflects increased liver enzymes and azotemia, respectively. Significant proteinuria and the increase in urine protein creatinine ratio revealed evidence of renal injury in dogs with IMHA.
Keywords: dogs; immune mediated hemolytic anemia; renal disease; Ehrlichia sp.; hematology